2002
DOI: 10.1038/oby.2002.87
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Month Tolerability of Orlistat in Adolescents with Obesity‐Related Comorbid Conditions

Abstract: MCDUFFIE, JENNIFER R., KARIM A. CALIS, GABRIEL I. UWAIFO, NANCY G. SEBRING, ERICA M. FALLON, VAN S. HUBBARD, AND JACK A. YANOVSKI. Three-month tolerability of orlistat in adolescents with obesity-related comorbid conditions. Obes Res. 2002;10:642-650. Objective: To study the safety, tolerability, and potential efficacy of orlistat in adolescents with obesity and its comorbid conditions. Research Methods and Procedures: We studied 20 adolescents (age, 14.6 Ϯ 2.0 years; body mass index, 44.1 Ϯ 12.6 kg/m 2 ). Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(89 citation statements)
references
References 53 publications
2
81
1
5
Order By: Relevance
“…For orlistat, published reports conclude repeatedly that it is 'well tolerated' [17][18][19]. However, published trial data show that although persistence with orlistat for Ն3 months in clinical trials was markedly greater than in our data, gastrointestinal side-effects were reported in >50%.…”
Section: Comparison With the Literaturecontrasting
confidence: 53%
See 1 more Smart Citation
“…For orlistat, published reports conclude repeatedly that it is 'well tolerated' [17][18][19]. However, published trial data show that although persistence with orlistat for Ն3 months in clinical trials was markedly greater than in our data, gastrointestinal side-effects were reported in >50%.…”
Section: Comparison With the Literaturecontrasting
confidence: 53%
“…However, gastrointestinal adverse events were reported by 50% of those taking orlistat [18]. A detailed study of the tolerability of taking orlistat together with a comprehensive behavioural and dietetic programme in 20 adolescents over 3 months found that 85% completed 3 months on orlistat, but that 50-60% reported a combination of unpleasant gastrointestinal side-effects [17]. In an early small open-label randomized controlled trial, gastrointestinal side-effects were reported in all 22 adolescents receiving orlistat, of whom seven (32%) dropped out of the trial during the first month of the trial due to side-effects attributable to orlistat [20].…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…In the US, the Food and Drug Administration (FDA) has approved orlistat for children aged 12-18 y in 2003 using a limited documentation with a maximum of 20 subjects in each study indicating the same side-effect profile as in adults. [53][54][55] However, until more extensive safety and efficacy data are available, medications for weight loss should be used only on an experimental basis in adolescents and children.…”
Section: Treatment Based On Psychotherapy Techniquesmentioning
confidence: 99%
“…Clinical trials in adults lasting up to 2 years have not reported serious side effects. 48 Recent studies in obese adolescents 49 and prepubertal children 50 indicate that short-term Orl treatment is well-tolerated by children and has a side effect profile similar to that observed in adults. Side effects are generally mild, are limited to gastrointestinal effects such as flatulence and oily leakage, and decrease with time.…”
Section: Discussionmentioning
confidence: 99%